2019
DOI: 10.15414/jmbfs.2019.8.4.1035-1040
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of Antagonistic Bacteria in the Management of Olive Knot Disease Caused by Pseudomonas Savastanoi Pv. Savastanoi

Abstract: Keywords: Pseudomonas savastanoi pv. savastanoi, olive knot disease, biological control, antagonistic bacteria, Bacillus subtilis 1240, Shimadzu) at 600 nm (El-kinany et al., 2017). Antagonistic strainsAll antagonistic strains belong to the collection of laboratory of plant bacteriology and Biological Control at the National Institute of Agronomic Research (Meknes, Morocco). Theirs origins, isolation dates, and references are described in Tab 1.Olive knot disease caused by Pseudomonas savastanoi pv. savastanoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…B. subtilis 2515-1 strain decreased the tumors in olive's stems caused by Pseudomonas savastanoi pv. Savastanoi 2064-8 strain [54]. B. subtilis QST 713 strain significantly reduced the percentage of latent infections of anthracnose on olive fruits, caused by Colletotrichum acutatum and Colletotrichum gloeosporioides [17].…”
Section: Beneficial Microorganisms Against Pathogensmentioning
confidence: 98%
See 3 more Smart Citations
“…B. subtilis 2515-1 strain decreased the tumors in olive's stems caused by Pseudomonas savastanoi pv. Savastanoi 2064-8 strain [54]. B. subtilis QST 713 strain significantly reduced the percentage of latent infections of anthracnose on olive fruits, caused by Colletotrichum acutatum and Colletotrichum gloeosporioides [17].…”
Section: Beneficial Microorganisms Against Pathogensmentioning
confidence: 98%
“…Over the last decade, PGPR (10 studies), endophytes (nine), and PGPF (six) have been the center of attention for their biocontrol potential against major olive plant diseases, whereas only two studies with AMF were conducted for this purpose (Table 3). Many strains of Bacillus and Pseudomonas have been used in agriculture as biocontrol agents against several diseases caused either by fungi or bacteria [54]. Sanei [55] reported that eight isolates of Pseudomonas fluorescens inhibited Verticillium's microsclerotia germination.…”
Section: Beneficial Microorganisms Against Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…R. aquatilis could survive at washing room of a minimally proceed plant with a temperature of 5°C and was not able to produce protease 29 . Also R. aquatilis, which had antagonistic activity against olive knot disease was not able to produce protease 30 , amylase and lipase. However, R. aquatilis in this study, was determined with protease, lipase and strong amylase activities, so until now, this is the first report of lipase production from cold-adaptive R. aquatilis.…”
Section: Discussionmentioning
confidence: 96%